2004
DOI: 10.3354/ame034239
|View full text |Cite
|
Sign up to set email alerts
|

Attachment mechanism in a highly specific association between ectosymbiotic bacteria and marine nematodes

Abstract: The marine Stilbonematinae (Nematoda) are known for their highly specific mutualistic association with thiotrophic ectosymbiotic bacteria. The mechanism mediating recognition and binding between symbionts and host was studied in 5 host species. When incubated with D-mannose and L-rhamnose the symbionts detached in 2 species, Laxus cosmopolitus and L. oneistus, most likely due to competitive interactions with sugars involved in the binding mechanism; 3 other species, Stilbonema maium, Eubostrichus topiarius and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 45 publications
(35 reference statements)
2
12
0
Order By: Relevance
“…Whether the folliculinid ciliate depends on symbionts has not yet been demonstrated. However, symbioses form between ciliates and chemoautotrophic bacteria in other reducing environments (Bauer-Nebelsick et al 1996, Nussbaumer et al 2004, and the very depleted values found here for the folliculinid ciliate corroborate unpublished SEM observations of bacteria covering the surface of this ciliate (C.R.F. unpubl.…”
Section: Symbiont-bearing Faunasupporting
confidence: 89%
“…Whether the folliculinid ciliate depends on symbionts has not yet been demonstrated. However, symbioses form between ciliates and chemoautotrophic bacteria in other reducing environments (Bauer-Nebelsick et al 1996, Nussbaumer et al 2004, and the very depleted values found here for the folliculinid ciliate corroborate unpublished SEM observations of bacteria covering the surface of this ciliate (C.R.F. unpubl.…”
Section: Symbiont-bearing Faunasupporting
confidence: 89%
“…This result suggested a high specificity and the occurrence of an acute recognition mechanism such as in nematode ectosymbioses (Nussbaumer et al, 2004). Moreover, molecular surveys indicated a bacterial community switch occurring between the first stages of the R. exoculata life cycle (egg and hatched egg libraries dominated by the Gammaproteobacteria) and later stages (juvenile/adult libraries dominated by the Epsilonproteobacteria) (Table 1), confirmed by FISH observations (Figures 2a and b versus d).…”
Section: Epibiont Diversity and Acquisitionsupporting
confidence: 62%
“…After 48 h, however, symbiontfree patches appeared on the worms, although the detached bacteria did not form visible aggregates in the surrounding media (data not shown). This may reflect the presence of free D-mannose, which is known to cause symbiont detachment, although with a much slower dynamic (i.e., dissociation starts only after 16 h and goes to completion after 90 h (22).…”
Section: Symbiont Binding To the Host Is Camentioning
confidence: 99%
“…Furthermore, this monosaccharide was found on the surface of the symbionts, but not on L. oneistus cuticle (22). These data led to the hypothesis that L. oneistus binds its symbionts by secreting a mannose-binding protein(s) from their posterior GSOs onto their cuticle.…”
mentioning
confidence: 91%